ANALISIS LEMBAR KERJA SISWA (LKS) BIOLOGI DI KOTA BINJAI YANG DIGUNAKAN SISWA KELAS VII SEMESTER GASAL 2018/2019 - MARLINDOAMAN SARAGIH (LP2MTBM MAKARIOZ, 2020)
Learning experiences can be gained by students through a series of activities by exploring the environment through activeinteractive with friends, the environment, and other resources. One of supporting means of learning that can be used toexplore the surrounding environment is with student worksheets (LKS). Increasing student activity is difficult by itselftherefore the role of teachers is indispensable to create a learning situation that is full of student activity of one of them usingLKS. The frequency of use of LKS is high enough in each learning should be balanced with high quality LKS as well.Generally junior high school students in Kota Binjai. The research uses the observation method by collecting data to obtaindescriptive price of Prosentase (DP) on the conformity of LKS content with KTSP and the level of obtaining an index ofactivation (IP) on the instructions of activities, drawings, or diagrams and exercise problems. Data analysis shows LKS 65%,medium category, student Activation index in the activity Directive of 0.03 which is relatively low, because it is in the range of0.40 – 1.50. IP on the image or diagram 1.37 which is classified as being in the range of 0.40 – 1.50. The activation indexof the 1.23 exercise questions is being in the range of 0.40 – 1.50. The cognitive realm is disproportionate, as C1 is moredominant at 40.8%. About the psychomotor domain P2 0.43% and P3 1.3%, no other level was found. The affective realm isnot found because it is difficult to apply affective content to the form of problems. The results of this research are expected tobe concrete information. For students and teachers to pay more attention to the LKS used. Similarly, for the author to paymore attention to aspects that support the quality of LKS such as the conformity of content LKS with the curriculum, the levelof activation of students and levels of exercise problems both cognitive, affective and psychomotor.